2022
DOI: 10.3390/diagnostics12081860
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient (ADC) Histogram Analysis in Parotid Gland Tumors: Evaluating a Novel Approach for Differentiation between Benign and Malignant Parotid Lesions Based on Full Histogram Distributions

Abstract: The aim of this study was to assess the diagnostic value of ADC distribution curves for differentiation between benign and malignant parotid gland tumors and to compare with mean ADC values. 73 patients with parotid gland tumors underwent head-and-neck MRI on a 1.5 Tesla scanner prior to surgery and histograms of ADC values were extracted. Histopathological results served as a reference standard for further analysis. ADC histograms were evaluated by comparing their similarity to a reference distribution using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[10][11][12] Constructing an evidence-based predictive mathematical model for disease diagnosis represents a new trend. [6][7][8] Some models for predicting benign and malignant parotid tumors have been described [6][7][8]13 ; however, most of the previous studies did not provide an easy-to-use and effective nomogram other than building a predictive mathematical model. In the present study, we combined the MR image features of parotid tumors and the basic clinical data of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Constructing an evidence-based predictive mathematical model for disease diagnosis represents a new trend. [6][7][8] Some models for predicting benign and malignant parotid tumors have been described [6][7][8]13 ; however, most of the previous studies did not provide an easy-to-use and effective nomogram other than building a predictive mathematical model. In the present study, we combined the MR image features of parotid tumors and the basic clinical data of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies to date have used histogram analysis to distinguish between benign and malignant lesions (8)(9)(10)(11), but the use of histogram analysis to distinguish BOLs and MOLs has not been reported in the literature. This study showed significant differences in most of the above histogram parameters used to distinguish BOLs and MOLs, including the mean value, coefficient of variation, skewness, and 1st, 5th, 10th, 25th, 50th, 75th, 90th, 95th, and 99th percentiles.…”
Section: Roc Analysismentioning
confidence: 99%
“…Thus, we can quantitatively analyze lesion features at the pixel level and obtain more objective and accurate information on subtle differences. As an effective method of image data analysis, histogram analysis is widely used in the differentiation, classification, and qualitative diagnosis of benign and malignant lesions (8)(9)(10)(11)(12)(13)(14)(15). The aim of the present study was to evaluate the usefulness of CT histogram analysis for differentiating benign osteoblastic lesions (BOLs) and malignant osteoblastic lesions (MOLs).…”
Section: Introductionmentioning
confidence: 99%